Comparison of energy intake and requirement of young students in Isfahan, Iran - Mehdi Tazhibi; Nimah Bahraini (Journal of Research in Medical Sciences, 2012)
Background: Estimation of energy intakes is required for understanding of growth and disease in young students. This study was conducted to estimate the energy intake of young students and compare with their energy requirements. Materials and Methods: In this cross-sectional study, using simple random sampling, 400 students, aged 14-18 years, were selected in 2010. Hariss-Benedict equations were used to estimate the energy requirement of each group. Results: Mean and standard error of energy intake and requirements of males was 2155 ± 30 and 1670 ± 18, respectively, and of females was 2700 ± 21, 2300 ± 4 kcal, respectively. Differences of means, energy intake, and requirement in both sexes were significant (P < 0.001). Conclusion: Because of their age (14-18 years), which is called growth age, energy intake was lower than their needs